Language, Power, and Pluralism: Decolonizing Islamic Discourse through Abu Zayd’s Hermeneutics - Ahmadi Ahmadi; A. Jauhar Fuad; Hamed A. Ead; Fahri Hidayat (Tribakti: Jurnal Pemikiran Keislaman, 2025)
This study aims to investigate how Nasr Hamid Abu Zayd employs language as a site of power and resistance in the reinterpretation of Islamic texts and the promotion of religious pluralism. It focuses on how his linguistic-hermeneutical approach challenges dominant literalist paradigms and contributes to the development of inclusive Islamic theology. The research adopts a qualitative methodology through textual analysis of Abu Zayd’s major works, complemented by a critical discourse analysis (CDA) framework. Key concepts such as language, power, and authority in interpretation are examined to understand how Abu Zayd reconstructs religious meaning within the context of sociopolitical realities. The findings reveal that Abu Zayd’s philosophy of language subverts literalist and hegemonic interpretations by promoting a dynamic, context-sensitive, and pluralistic reading of Islamic texts rooted in lived human experience. His hermeneutics exposes the embedded power relations in religious discourse and offers a critical lens for deconstructing interpretative authority. By foregrounding the role of language in shaping theological narratives, this study contributes to the decolonization of Islamic discourse and highlights Abu Zayd’s hermeneutics as a foundation for developing an emancipatory and pluralist Islamic theology, particularly relevant for Muslim communities beyond the dominant Arab-Western paradigms. This research contributes to the decolonization of Islamic studies by demonstrating how linguistic awareness and interpretive plurality can challenge hegemonic discourses, reclaim interpretative agency, and open new spaces for contextual and inclusive Islamic thought, especially within postcolonial Muslim societies.